Evaluating e-Government and Good Governance Correlation - Suhardi Suhardi; Alfira Sofia; Agustinus Andriyanto (LPPM ITB, 2015)
Assessing the achievement of Indonesian government institutions in implementing e-government has been conducted since around a decade ago. Several national assessments are available with almost the same ranking results. There is an agreement that the ultimate goal of e-government implementation is to achieve good government governance (GGG), while success stories of e-government require good governance practices. This study explored the correlation between e-government achievement and GGG achievement in Indonesia. Spearman's rank correlation was used to characterize the relationship strength between e-government assessment results and good governance assessment results. The data were collected from institutions that participated in e-government and good governance assessments. The results showed that the correlation between these two entities is not very strong. Most cases showed that e-government implementation and the achievement of good governance have only a moderate positive correlation and none of the studied cases indicated a significant connection. This result can be attributed to the lack of emphasis on goals achievement in the assessments. Thus, it is recommended that future Indonesian e-government assessments should involve impact indicators.